Worth it? The usefulness of information technology to read ID cards and passports for hoteliers in Bulgaria - Stanislav Ivanov; Christopher Russell (Tourism and Hospitality Management, 2018)
Purpose – The case study investigates whether a particular IT is worthwhile, in view of its perceived, potential and actual usefulness. It answers two research questions: How necessary is an automated ID card/passport reader for hoteliers? and Which characteristics of such software do hoteliers most favour? Design – Data collection took place in 2013 through an online questionnaire. The sample includes 70 hotel managers in Bulgaria. Methodology – Kruskal-Wallis χ2 test and Wilcoxon signed ranks test were used in the data analysis. Approach – The case study adopted survey as a research strategy. The sample includes only respondents from Bulgaria. Hence, findings are generalisable only in this cultural setting. Findings – Findings revealed that the most important software characteristics desired by hotel managers are: quality, price, easy to use interface, speed, integration with the existing hotel software and completeness of the extracted data. However, results suggest that there is little necessity of an automated ID card reader due to limited time savings offered by the new technology and few mistakes during the manual entry of ID card/passport data in the information systems of hotels. Originality of the research – This empirical research practically assesses the viability of specific technology adoption by hoteliers in Bulgaria. This research was implemented by the authors in response to a request by a company that produces software for ID card/passport readers. The results helped the company in its product launch and follow-up marketing strategy.